Peningkatan Prestasi Belajar Siswa Pada Mata Pelajaran SKI Melalui Media Video Pembelajaran - Endarwati, Suci; Darim , Abu (ILJ: Islamic Learning Journal, 2025)
This article discusses the integration of improving student learning achievement in SKI subjects through educational videos at MTs Assholach Pasuruan. This research was conducted by interviewing the head of the madrasah, SKI subject teachers, and students. Data was collected through observation, interviews, and documentation. This research is a qualitative study using a case study approach, with data analysis conducted from the time the researcher determined the focus of the study until the research report was compiled. There are three stages in qualitative research analysis that occur simultaneously, including data reduction, data presentation, and conclusion drawing, or what can be referred to as verification. The results of the study show that the use of video media in SKI learning at MTs Assholach Pasuruan has proven to be effective in improving student learning achievement. Planning was carried out collaboratively, implementation used participatory methods, and evaluation showed an increase in student interest, understanding, and religious character. Video media not only facilitates understanding of the material but also shapes critical, active, and Islamic attitudes, although improvements in group management are still needed.